INTEGRITATEA VALORILOR MORALE ÎN GÂNDIREA LUI C. S. LEWIS (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Abstract: The Integrity of Moral Values in the Thought of C.S. LewisClive Staples Lewis’s reflections about the „abolition of man” – the abolition of morals and human conscience – are amazingly relevant in our contemporary culture, shaped by an ongoing moral relativism. Our aim in this paper is, therefore, to emphasize the necessity to protect the integrity of moral values. Specifically, we will describe the concept of Tao; secondly, we take notice of some of the perils which threaten the integrity of moral values and, subsequently, of human conscience itself – challenges which are even greater than in the year of 1943, when C.S. Lewis published the Abolition of Man – and finally, we will uncover a few solutions that humans can use as they pass through these challenges.